Scientific Crime Investigation: A Comparison of The Indonesia Criminal Justice System and Malaysia Legal Practice - Harefa, Beniharmoni; Nazli Bin Ismail (Veteran Law Review, 2025)
The criminal justice system in Indonesia faces the challenge of delivering fair and objective decisions through strong and valid evidence. Therefore, the presence of Scientific Crime Investigation (SCI) offers a new, more accurate approach to uncovering criminal facts through forensic technology and scientific analysis. Although SCI has great potential to influence court decisions, its implementation in Indonesia still requires improvement to be more effective. Therefore, this study aims to determine the influence of evidence generated from SCI on court decisions and the problems faced in implementing SCI in Indonesia. The research method used is normative legal research. Further, a comparative analysis with the position in Malaysia is included to derive valuable insights as to how SCI is governed in the neighboring country. Based on the results of the study, it shows that the implementation of SCI is essential to create an accurate and effective justice system by strengthening judges' confidence in decision-making. However, investment in forensic infrastructure, improving the quality of human resources, and strengthening regulations are needed so that SCI can function as a central tool of evidence, replacing less effective conventional methods.